Findings From Somatic and Cerebral Near-Infrared Spectroscopy and Echocardiographic Monitoring During Ductus Arteriosus Ligation: Description of Two Cases and Review of Literature - Michel-Macías, Carolina; Morales-Barquet, Deneb Algedi; Martínez-García, Alfonso; Ibarra-Ríos, Daniel (Frontiers in Pediatrics, 2020)
Background: Preterm infants with hemodynamically significant patent ductus arteriosus (HsPDA) are exposed to low cerebral tissue oxygen saturation (rScO2) values. Additionally, infants requiring surgical ligation are at risk of further changes in cerebral oxygenation and postligation cardiac syndrome (PLCS). Previous studies have assessed the effect of PDA ligation on rScO2 with variable results. Cases description: In this report we analyze near-infrared spectroscopy (NIRS) and echocardiographic findings of two patients who underwent ligation of PDA and presented low cardiac output. Literature on regional tissue oxygenation saturation (rSO2) before and after PDA ligation was briefly reviewed. Discussion: Cerebral oxygenation values before and after PDA ligation may be influenced by gestational age, vasopressor use, ductal shunt volume, time of exposure HsPDA, chronological age and the presence of cerebral autoregulation. PLCS complicates 28-45% of all PDA ligations and is associated with higher mortality. Cerebral and somatic NIRS monitoring in the postoperative period may enhance the identification of PLCS at early stages. Conclusion: A prospective cohort study is recommended to evaluate the utility of two-site NIRS monitoring in the detection of PLCS. NIRS values should be interpreted as trends along with echocardiographic findings to guide goal directed interventions.